Leadership Behavior in Implementing the Mental Revolution for Improving Teacher Performance - Herinto Sidik Iriansyah; Iswadi Iswadi (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aimed to determine the principal's leadership behavior in implementing mental revolution to improve teacher performance at SMK Islam PB Soedirman 2 Jakarta. Research using a qualitative approach with data collection techniques documentation, observation, and interviews. The research subjects were the principal and the teacher. This research shows that the formulation of principal policies in implementing mental revolutions to improve teacher performance at SMK Islam PB Soedirman 2 Jakarta has made written and oral rules according to the vision and mission of the school. It involves teachers, school targets, and school principals in formulating activities to improve teacher skills. These results make teachers better understand the lessons more easily and feel comfortable during school and achieve better quality education. As a leader in implementing a mental revolution to improve teacher performance at SMK Islam PB Soedirman 2 Jakarta, the principal's program is done by good communication. It is not rude, direct supervision, not arrogant and authoritarian, compiling a KKG program, seminars, and the workshop with this program shows encouraging results. Teachers are more disciplined to complete their assignments well. The principal's strategy is to involve all teachers and provide direct examples. The factors that influence the principal's leadership in implementing a mental revolution to improve teacher performance are his desire to improve school performance. This is the main factor that influences it along with other general factors, such as the personal condition of the principal, school organization, the external environment.